5-(4-Chlorophenyl)-1-cyclopropyl-2-(2-fluorophenyl)-3-phenylpentane-1,5-dione - Srinivasan, Thothadri (International Union of Crystallography, 2013)
In the title compound, C(26)H(22)ClFO(2), the cyclopropane ring makes dihedral angles of 45.7 (2), 49.0 (2) and 65.2 (2)° with the fluoro-substituted phenyl ring, the benzene ring and the chloro-substituted phenyl ring, respectively. The F and Cl atoms deviate by 0.0307 (11) and 0.0652 (6) Å, respectively, from the planes of the phenyl rings to which they are attached. In the crystal, molecules are linked by C—H⋯F hydrogen bonds, forming chains along the b axis.